STRATEGI KEUANGAN MATRIKS SEBAGAI ALAT BANTU KEPUTUSAN INVESTASI DAN PEMBIAYAAN - Purnamasari, Raeny; Suci, Rahayu Puji; Handini, Dharmayanti Pri (JURNAL MANAJEMEN DAN AKUNTANSI, 2013)
Abstract: This study aims to determine the financial strategy matrix on Myoh Technology Tbk. which consists of Return on Invested Capital (ROIC), Cost of Capital (WACC), and Economic Value Added (EVA). And provide suggestions for aligning corporate strategy in the companys growth with investment and financing decisions, and to determine the appropriate strategies to quadrants where companies are grouped in the context of investment and financing decisions. Determination is the subject of research in 2006 to 2011 Myoh Technology Tbk. Ranking frequent bottom of the five companies went public in the same field in terms of total assets, shareholders equity, total liabilities and net profit. The results of this study are derived after calculating EVA and cash surplus or defist then grouped into four quadrants according to the financial strategy matrix. In Table quadrant matrix known that. Myoh Technology Tbk. the period 2007-2011, in the year 2007 until the year 2009 entered the fourth quadrant, due to the cash deficit and EVA <0. Whereas in 2010 entered as cash deficit quadrants one and EVA> 0. As well as in 2011 entered the quadrant two, because of a cash surplus and EVA> 0 Keywords: finance strategy matrix, ROE, EVA